Treatment patterns, outcomes and healthcare resource utilization of obstructive hypertrophic cardiomyopathy in England - Faizel Osman; Carla L. Zema; Michael Hurst; Belinda Sandler; Florence Brellier; Ovie Utuama; Oksana Kirichek; John Houghton; Teresa Lemmer; Maite Tome Esteban (ESC Heart Failure)
Abstract Aims Describe patient characteristics, treatment patterns, clinical outcomes, healthcare resource utilization (HCRU) and medical costs associated with patients who were diagnosed with obstructive hypertrophic cardiomyopathy (HCM) in clinical practice in England. Methods and results This observational, retrospective, cohort study of adults who were diagnosed with obstructive HCM in routine clinical practice in England used electronic health records from Clinical Practice Research Datalink (CPRD) GOLD/Aurum and linked Hospital Episode Statistics (HES) databases (1 April 2007 to 30 October 2020). Adults (≥18 years at index date) with at least one diagnosis code (ICD‐10, Read, SNOMED, or OPCS) indicative of HCM with ≥1 year of continuous registration in CPRD, data of acceptable research quality and eligibility for HES linkage were included. Outcomes from the obstructive HCM cohort were stratified by New York Heart Association (NYHA) class at baseline and during follow‐up. Owing to the paucity of NYHA coding, patients with obstructive HCM and no record of NYHA class were assigned a proxy NYHA classification using an algorithm that considered patient symptoms and treatments. The study included 6440 patients in the overall HCM cohort with a mean follow‐up duration of 4.84 [standard deviation (SD): 2.95] years. The study population was predominantly male (61.9%) and white (79.1%), with a mean (SD) age of 61.02 (15.61) years. The proportion of patients with obstructive HCM who had a pre‐specified prior medical condition relevant to understanding disease burden increased with higher NYHA class (66.5% vs. 83.0% for NYHA class I and NYHA class II+, respectively), as did the proportion of patients with at least one baseline active prescription for cardiovascular‐related medication. Among patients with at least one record of a prescription for the treatment of symptomatic obstructive HCM, 41.7% experienced a treatment change during the follow‐up period. Atrial fibrillation or flutter, ischaemic stroke and heart failure were the most observed clinical events among patients in the obstructive HCM cohort, and the first in‐study incidence of these events increased with higher NYHA class. Total HCRU costs per patient‐year increased from £3033 to £4517 for NYHA classes I and II+, respectively, with secondary care costs consistently being the main driver in the obstructive HCM cohort. Conclusions Obstructive HCM is associated with a large clinical and economic burden in England, and this burden increases with higher NYHA class. These findings support the need for new and more effective strategies for the management of HCM.